2008
DOI: 10.1002/jbt.20227
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine can pre‐ and post‐condition heart and utilizes a different mechanism from sphingosine 1‐phosphate

Abstract: Consistent with previous reports, sphingosine at a high concentration (5 microM) was cardiotoxic as evidenced by increased infarct size in response to ischemia/reperfusion in an ex vivo rat heart. Sphingosine 1-phosphate (S1P) at 5 microM was cardioprotective. However, at a physiologic concentration (0.4 microM) sphingosine as well as S1P was effective in protecting the heart from ischemia/reperfusion injury both when perfused prior to 40 min of ischemia (preconditioning) or when added to reperfusion media fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
48
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 26 publications
11
48
0
1
Order By: Relevance
“…1). As previously shown (32)(33)(34)(35), the recovery of hemodynamic function, assessed as LVDP, is poor, and at the end of 40 min of reperfusion, these hearts have large areas of infarction by TTC staining. Treating ex vivo hearts at the midpoint of the equilibration period (before ischemia) with a 1-min perfusion of 0.4 M ATP greatly improved the recovery of LVDP during reperfusion (79 Ϯ 5% of its preischemic value compared with 6 Ϯ 2% for 1 min buffer treatment).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…1). As previously shown (32)(33)(34)(35), the recovery of hemodynamic function, assessed as LVDP, is poor, and at the end of 40 min of reperfusion, these hearts have large areas of infarction by TTC staining. Treating ex vivo hearts at the midpoint of the equilibration period (before ischemia) with a 1-min perfusion of 0.4 M ATP greatly improved the recovery of LVDP during reperfusion (79 Ϯ 5% of its preischemic value compared with 6 Ϯ 2% for 1 min buffer treatment).…”
Section: Resultssupporting
confidence: 61%
“…PI3K and Akt are important components of the cardioprotection signaling pathway that leads to the key cell survival molecule phospho-Akt (11,17,23,24,34,37). As reported previously (37) and shown in Fig.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This study shows that 0.5 M apelin-13 protects the rat heart only when infused during the first 20 min of reperfusion but not when given before ischemia. Thus, whereas several compounds mimic both preC and postC (12,44,48), apelin-13 mimics postC only.…”
Section: Is Apelin a Prec Or A Postc Mimetic?mentioning
confidence: 98%
“…Although there is abundant evidence that sphingosine is toxic to cells [25,28] , diverse function by concentration dependence of sphingosine has been reported. Vessey et al [35] recently reported that at lower dose (submicromolar), a more physiologic concentrations, sphingosine has been shown to be cardioprotective in isolated Langendorff-perfused rat hearts subjected to ischemia/reperfusion injury. Unlike S1P, sphingosine-induced cardioprotection seems to be mediated by cyclic nucleotide-dependent protein kinase A and G (PKA and PKG) pathways [35] .…”
Section: Sphingosinementioning
confidence: 99%